2010
DOI: 10.1142/s0217732310032639
|View full text |Cite
|
Sign up to set email alerts
|

Towards Special Daemon-Sensitive Electron Multiplier: Positive Outcome of March 2009 Experiment

Abstract: Results of the experiments on daemon detection performed in St-Petersburg in March 2009 are presented. Adding the data obtained with the daemon-sensitive FEU-167-1 PM tubes to the data amassed in our previous measurements (starting from 2000) raises the confidence level of existence of the spring maximum in NEACHO (near-Earth almost circular heliocentric orbit) daemon flux to ~5σ.The first test experiments conducted with the "dark" electron multiplier tubes, -TEU-167 with a thick (~0.5 µm) Al coating over all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…Among the many DM candidates we recall: SUSY particles (as e.g. neu-tralino [58][59][60][61][62][63][64][65][66][67][68] or sneutrino in various scenarios [69][70][71][72] ), inelastic Dark Matter in various scenarios, [73][74][75][76] electron interacting Dark Matter (also including some WIMP scenarios), 77,78 a heavy neutrino of the 4-th family, sterile neutrino, 79 Kaluza-Klein particles, self-interacting Dark Matter, 80 axion-like (light pseudoscalar and scalar candidate), 81 mirror Dark Matter in various scenarios, [82][83][84] Resonant Dark Matter, 85 DM from exotic 4th generation quarks, 86 Elementary Black holes, [87][88][89][90] Planckian objects, [87][88][89][90] Daemons, [87][88][89][90] Composite DM, 91,92 Light scalar WIMP through Higgs portal, 93 Complex Scalar Dark Matter, 94 specific two Higgs doublet models, exothermic DM,…”
Section: Dm Candidatesmentioning
confidence: 99%
“…Among the many DM candidates we recall: SUSY particles (as e.g. neu-tralino [58][59][60][61][62][63][64][65][66][67][68] or sneutrino in various scenarios [69][70][71][72] ), inelastic Dark Matter in various scenarios, [73][74][75][76] electron interacting Dark Matter (also including some WIMP scenarios), 77,78 a heavy neutrino of the 4-th family, sterile neutrino, 79 Kaluza-Klein particles, self-interacting Dark Matter, 80 axion-like (light pseudoscalar and scalar candidate), 81 mirror Dark Matter in various scenarios, [82][83][84] Resonant Dark Matter, 85 DM from exotic 4th generation quarks, 86 Elementary Black holes, [87][88][89][90] Planckian objects, [87][88][89][90] Daemons, [87][88][89][90] Composite DM, 91,92 Light scalar WIMP through Higgs portal, 93 Complex Scalar Dark Matter, 94 specific two Higgs doublet models, exothermic DM,…”
Section: Dm Candidatesmentioning
confidence: 99%
“…This conclusion was supported by our reconnaissance underground experiments at Baksan, in which the triggering pulse was initiated by an HPS excited by a daemon in the ZnS(Ag) screen and the second, time-shifted pulse characterizing the daemon velocity was created by a light-insulated FEU-167 with increased thickness of the inner Al coating [19]. These experiments naturally suggested that the second, short pulse with an NLS shape was presumably created in our first experiments [1] in the lower FEU-167 itself, without the lower ZnS(Ag) scintillation screen being involved [3]. Therefore, a good reproducibility of these results would not be expected in replication of detectors of this kind with PMTs of other types (or even the same devices from other manufacturers) [3].…”
Section: Dark Electron Multiplier a New Device For Detection Of Daemonsmentioning
confidence: 77%
“…These experiments naturally suggested that the second, short pulse with an NLS shape was presumably created in our first experiments [1] in the lower FEU-167 itself, without the lower ZnS(Ag) scintillation screen being involved [3]. Therefore, a good reproducibility of these results would not be expected in replication of detectors of this kind with PMTs of other types (or even the same devices from other manufacturers) [3].…”
Section: Dark Electron Multiplier a New Device For Detection Of Daemonsmentioning
confidence: 89%
See 2 more Smart Citations